Effect of Curing Temperature on Mechanical Properties of Sanitary Ware Porcelain based Geopolymer Mortar - Woratid Wongpattanawut; Borvorn Israngkura Na Ayudhya (Salehan Institute of Higher Education, 2023)
The objective of this study was to investigate the effect of curing temperature on the mechanical properties of sanitary ware porcelain powder-based geopolymer paste and mortar under various curing temperatures. The setting time, porosity, water absorption, and compressive strength of specimens mixed with alkaline concentrations of 8M, 10M, 12M, and 14M were compared. All mortar cube (50×50×50 mm) specimens were placed into drying ovens for 24 hours at 60°C, 75°C, 90°C, and 105°C, respectively. The specimens were then air-cured for 1, 3, 7, 14, and 28 days. The results showed that the elevated curing temperature accelerated the polymerization process of the porcelain geopolymerization reaction. The setting time varied between 89 mins and 380 mins. It showed variability depending on alkaline concentration and initial curing temperature. The setting time of pastes decreased when alkaline concentrations increased. An increasing temperature in the drying oven decreased the initial and final setting times. Similar to this, the rate of water absorption and permeability of porcelain-based geopolymer mortar specimens decreased with drying oven temperatures and increments in alkaline concentration. The lowest water absorption and porosity of the specimen were 2.1% and 15.7%, respectively. The compressive strength increased as drying oven temperatures and alkaline concentrations increased. The highest 28 day compressive strength was found in 14M specimens with 105°C curing temperatures. The ultimate compressive strength was 64.45 N/mm2. Scanning electron microscopy (SEM) and X-ray diffraction (XRD) were investigated to study the microstructural properties of the geopolymers. Doi: 10.28991/CEJ-2023-09-08-01 Full Text: PDF